Association between SYNTAX II score and Index of electrophysiological balance in patients with stable angina pectoris - Alsancak, Yakup; Sertdemir, Ahmet; Duran, Mustafa; Gürbüz, Ahmet Seyfeddin; İçli, Abdullah (Journal of Surgery and Medicine, 2022)
Background/Aim: Syntax II scoring system has been established by integrating anatomical features and clinical characteristics of patients in order to achieve better prediction of post-procedural outcomes. On the other hand, its predictive value for the occurrence of life-threatening arrhythmias is inconclusive. Index of cardio electrophysiological balance (iCEB) serve as an ECG based derivative of cardiac wave length and associated with torsades de pointes (TdP) and nontorsadogenic ventricular tachycardia (VT) or ventricular fibrillation (VF). In this study we aimed to investigate the prognostic value of SYNTAX II scoring system for predicting malignant ventricular arrhythmias by using iCEB. Methods: 297 patients undergoing coronary angiography (CAG) were included in the retrospective cohort study. Patients were divided into two groups based on their calculated SYNTAX Score II. For each group, ECG parameters including heart rate (b.p.m.), QRS interval (ms), QT interval (ms), corrected QT (QTC) interval (ms), QTc difference (V1-V6), QT/QRS ratio (iCEB) and QTC/QRS ratio (iCEBc) were analyzed. Results: According to our study estimated QRS, QT and QTc intervals were signifciantly higher in patients with calculated SYNTAX S II >26 as compared to patients with calculated SYNTAX S II ≤26 (respectively; P=0.001, P=0.014 and P=0.001). In addition, estimated QT/QRS (iECB) and QTc/QRS (iECBc) ratio were significantly lower in patients with calculated SYNTAX S II >26 as compared to those with calculated SYNTAX S II ≤26 (respectively; P=0.002 and P=0.005). Conclusion: Our data showed that, there was a strong association between QTC, iECB, iECBc and SYNTAX Score II. Therefore, the SYNTAX Score II might be considered as an important tool to predict malignant ventricular arrhythmias.